Immunological analysis of hybrid neoantigen peptide encompassing class I/II neoepitope-pulsed dendritic cell vaccine - Morisaki, Shinji; Onishi, Hideya; Morisaki, Takafumi; Kubo, Makoto; Umebayashi, Masayo; Tanaka, Hiroto; Koya, Norihiro; Nakagawa, Shinichiro; Tsujimura, Kenta; Yoshimura, Sachiko; Yew, Poh Yin; Kiyotani, Kazuma; et al. (Frontiers in Immunology, 2023)
Neoantigens are tumor-specific antigens that evade central immune tolerance mechanisms in the thymus. Long-term tumor-specific cytotoxic T lymphocyte activity maintenance requires class II antigen-reactive CD4 + T cells. We had previously shown that intranodal vaccination with class I neoantigen peptide-pulsed dendritic cells (DCs) induced a robust immune response in a subset of patients with metastatic cancer. The present study aimed to perform a detailed ex vivo analysis of immune responses in four patients receiving an intranodal hybrid human leukocyte antigen class II neoantigen peptide encompassing a class I neoantigen epitope (hybrid neoantigen)-pulsed DC vaccine. After vaccination, strong T-cell reactions against the hybrid class II peptide and the class I-binding neoantigen peptide were observed in all four patients. We found that hybrid class II neoantigen peptide-pulsed DCs stimulated CD4 + T cells via direct antigen presentation and CD8 + T cells via cross-presentation. Further, we demonstrated that hybrid class II peptides encompassing multiple class I neoantigen epitope-pulsed DCs could present multiple class I peptides to CD8 + T cells via cross-presentation. Our findings provide insight into the mechanisms underlying hybrid neoantigen-pulsed DC vaccine therapy and suggest future neoantigen vaccine design.